If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + 2c + -5 + -5c = 7 Reorder the terms: -5 + c + 2c + -5c = 7 Combine like terms: c + 2c = 3c -5 + 3c + -5c = 7 Combine like terms: 3c + -5c = -2c -5 + -2c = 7 Solving -5 + -2c = 7 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -2c = 7 + 5 Combine like terms: -5 + 5 = 0 0 + -2c = 7 + 5 -2c = 7 + 5 Combine like terms: 7 + 5 = 12 -2c = 12 Divide each side by '-2'. c = -6 Simplifying c = -6
| 3(2m-3)=8(m+1) | | x^3+5x^2+7x+35= | | 1.2(4x-3.2)=2 | | 2x-4(x+2)=x(2x-1) | | (7x+3)=6 | | 6C(12)=48 | | (7x+3)= | | (4x-10x)-40+3=2(x-1) | | 5z-4z=48 | | 1x=2x-7 | | 2x-37=24 | | 3x^2-x=5 | | X=2x-7 | | 2x-3y=24 | | 6t-6=9t-36 | | k^2+4k-77=0 | | -9.3x+1.8=-52.8-1.5x | | 3.5+2x+5.5=10 | | 4x-10x-40+3=2(x-1) | | 7x+3x=6 | | (7)m-(9)m=(-12) | | x^2+5x+10=0 | | 3(w-2)-6w=-21 | | -2.06d+18=-10.48 | | 3a=144 | | 7m-9m=-12 | | x^2(x+9)+7(x+9)= | | -110=-4c-6c | | 3b+4=15 | | 5x+10=3x+24 | | 11x+(-6x)+11= | | 9r-8=6r+7 |